x^2 - 5x + 6 =< 0

First let us factor:

(x-3)(x-2) =< 0

Then we have two cases:

case 1:

x-3 =< 0 and x-2 => 0

x =< 3 and x => 2

==>** x = [ 2, 3] **

case 2:

x-3 => 0 and x-2 =< 0

==> x => 3 and x =< 2 (impossible)

then the solution is:

**x = [2, 3]**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now